Pelatihan Tazkiyatun Nafs pada Karyawan Rumah Bersalin Cuma-Cuma Bandung: Tazkiyatun Nafs Training For Staff in the Maternity Hospital Cuma-Cuma, City of Bandung - Rohmah, Nur; Rahmilasari, Giari; Humnah, Habibah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Length of service, shift work, psychosocial problems included in the workload, and physical activity significantly influence how employees cope with fatigue and provide services. Handling these issues can be done with a holistic approach that does not separate spirituality from its implementation. Tazkiyatun nafs training aims to exercise self-control through tazkiyyatun nafs to increase employees' Islamic Religious Coping. The method of activities is a tazkiyatun nafs workshop that invites religious experts (experts in Islamic aqidah philosophy, Qur'an interpretation, and hadith interpretation). The training was conducted four times in one month and was equipped with a study of muhasabah verses and daily worship practices with 21 participants, but only 13 people completed the form. At the end of the session, an evaluation was conducted using the Islamic Religious Coping Short Form Positive instrument. Participants' Religious Coping showed a significant average increase from an average of 182.08 to 182.31. This training is expected to increase religiosity or good spirituality and face problems calmly, not labile and easily anxious, because religious coping born from spiritual strength can arouse a sense of confidence and optimism.